Epidemiology and risk factors of colorectal cancer in China - Yang, Yong (Chin J Cancer Res, 2020)
In China, colorectal cancer (CRC) ranked fourth and fifth in the highest incidence and mortality rates of all malignancies in 2018, respectively. Although these rates are below the world average, China placed first worldwide in the number of new CRC cases and CRC-related deaths because of its comparatively large population. This disease represents a threat to the health of population and incurs a heavy economic burden on the society and individuals. CRC has various risk factors, including age, sex, lifestyle, genetic factors, obesity, diabetes, gut microbiota status, and precancerous lesions. Furthermore, incidence and mortality rates of CRC are closely related to socioeconomic development levels, varying according to regional and population characteristics. Prevention is the main strategy to reduce incidence and mortality rates of CRC. This can be achieved through strategies stimulating lifestyle changes, healthy diet habits, and early screening for high-risk individuals. To reduce the burden of CRC, public health officials should promote prevention and management of modifiable risk factors through national policies. The rising incidence and mortality rates of CRC in China may be timely curbed by clarifying specific epidemiological characteristics, optimizing early screening strategies, and strictly implementing diagnosis and treatment guidelines. Thus, this study aimed to collect and report the current research status on epidemiology and risk factors of CRC in China.